2016
DOI: 10.1139/apnm-2015-0551
|View full text |Cite
|
Sign up to set email alerts
|

Protein requirement in critical illness

Abstract: How much protein do critically ill patients require? For the many decades that nutritional support has been used there was a broad consensus that critically ill patients need much more protein than required for normal health. Now, however, some clinical investigators recommend limiting all macronutrient provision during the early phase of critical illness. How did these conflicting recommendations emerge? Which of them is correct? This review explains the longstanding recommendation for generous protein provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
0
22
0
6
Order By: Relevance
“… There is a lack of randomized controlled trials (RCTs) that evaluate critically ill patients randomized to different doses of protein provision, adjusted for ideal energy intake, and then followed for long‐term clinical outcomes 35 , 36 Protein and calorie doses are typically recommended based on actual body weight 24 , 37 .…”
Section: Protein Requirements In the Icumentioning
confidence: 99%
“… There is a lack of randomized controlled trials (RCTs) that evaluate critically ill patients randomized to different doses of protein provision, adjusted for ideal energy intake, and then followed for long‐term clinical outcomes 35 , 36 Protein and calorie doses are typically recommended based on actual body weight 24 , 37 .…”
Section: Protein Requirements In the Icumentioning
confidence: 99%
“…Recognizing that widely used EN regimens systematically fall short of their nutrition target, clinical investigators in several centers carried out large randomized clinical trials (RCTs) that compared standard (inadequate) EN with the same EN supplemented with PN that infused large amounts of dextrose but very little protein substrate. When these trials indicated no overall difference in clinical outcomes, a high‐profile clinical practice review endorsed “permissive underfeeding” (protein‐deficient low‐energy EN) for at least the first week of a patient's stay in an intensive care unit (ICU), on the grounds that there is no good evidence that doing otherwise improves clinical outcomes . In agreement with this conclusion, ASPEN suggests tolerating a week or longer of permissive underfeeding before initiating PN in critically ill patients in whom EN has failed to achieve its goal (weak recommendation, very‐low‐quality evidence)…”
Section: Evolution Of Critical Care Nutritionmentioning
confidence: 99%
“…Differing magnitudes of these 3 effects, ie, sicker patients are more difficult to feed enterally, protein dose, and energy substrate resistance, coupled with the failure or inability of authors to identify or adjust for them in their analyses, may well explain why permissive underfeeding is associated with better outcomes in some observational studies but worse outcomes in others. The clinching evidence for this conclusion is provided by the many RCTs that compared high‐energy, protein‐deficient SNS with low‐energy, protein‐deficient SNS (permissive underfeeding) and found it of little or no benefit . In conclusion, the benefits of permissive underfeeding, when they occur, are not due to protein deprivation, but rather because it avoids energy overfeeding.…”
Section: Permissive Underfeeding and Clinical Outcomesmentioning
confidence: 99%
“…The results have been very disappointing. The flawed logic of this calorie-focused approach has been analyzed elsewhere [22,25,26]. The hypothesis that continues to await rigorous testing is that prompt, high-protein (2–2.5 g/kg per day) hypocaloric nutrition may improve clinical outcomes in catabolic critical illness.…”
Section: Effects Of Starvation and Disease On Protein Metabolism Amentioning
confidence: 99%